EVALUASI KEBERHASILAN PENGGUNAAN SISTEM INFORMASI MANAJEMEN KEUANGAN DAERAH DITINJAU DARI OPINI BPK-RI - , Nur Budiyanto ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Evaluation is the one of the important aspect to justify the succesfull implementation of information system. Evaluation can be used to improve the information system through past experience, to find technique or effective method, to investigate failure and learn from past experience. This research is to evaluate implementation of âSistem Informasi Manajemen Keuangan Daerah (SIMDA)â justified from BPK-RI opinion with HOT-Fit model. This research will measure the succesfull implementation of SIMDA. This research was conducted with total 38 respondent at BPK-RI Perwakilan Banten and four local government. For data analysis method, this research used Partial Least Square (PLS) using the software SmartPLS. The test result with Î¬=0,10 indicates that the system use is significantly influenced by system quality. Net benefits is significantly influenced by technology.